THE RUBBER REINFORCED SUPPORT PARTS FOR COMPLEITING DYNAMICS AND QUIESCENT LOADS OF BRIDGE CONSTRUCTIONS - Skokov, O. I.; Dyachenko, O. H.; Volovschikova, V. V.; Khorolsky, M. S. (Science and Transport Progress, 2010)
The research of deformation characteristics of the rubber reinforced support parts (RRBP), which compensate static and dynamic loadings of elements of bridge constructions, is conducted. The technology for manufacturing RRBP using new materials is developed; their deformation characteristics are investigated with the purpose of determination of the predicted operation life.